Acoustic Droplet Printing Tumor Organoids for Modeling Bladder Tumor Immune Microenvironment within a Week. Issue 22 (23rd September 2021) - Gong, Zhiyi; Huang, Lanxiang; Tang, Xuan; Chen, Keke; Wu, Zhuhao; Zhang, Lingling; Sun, Yue; Xia, Yu; Chen, Hui; Wei, Yongchang; Wang, Fubing; Guo, Shishang
Abstract: Current organoid models are limited by the incapability of rapidly fabricating organoids that can mimic the immune microenvironment for a short term. Here, an acoustic droplet‐based platform is presented to facilitate the rapid formation of tumor organoids, which retains the original tumor immune microenvironment and establishes a personalized bladder cancer tumor immunotherapy model. In combination with a hydrophobic substrate, the acoustic droplet printer can yield a large number of homogeneous and highly viable bladder tumor organoids in vitro within a week. The generated organoids consist of all components of bladder tumor, including diverse immune elements and tumor cells. By coculturing tumor organoids with autologous immune cells for 2 days, tumor reactive T cells are induced in vitro. Furthermore, it is also demonstrated that these tumor‐reactive T cells can also enhance the killing efficiency of matched organoids. Because of the easy operation, repeatability, and stability, the proposed acoustic droplet platform will provide a reliable approach for personalized tumor immunotherapy. Abstract : The acoustic droplet printing platform consists of an acoustic surface wave droplet printing device and a bionic structured hydrophobic substrate, allowing rapid preparation of a bladder tumor organoid that preserves the tumor immune microenvironment within one week, and in vitro expansion of tumor‐reactive T cells after 2 days of coculture with autologous‐derived immune cells.